A Case of Carcinosarcoma of the Peritoneum With Serous Tubal Intraepithelial Carcinoma - Akiko Kanemura; Tohru Morisada; Mai Momomura; Fumio Asano; Hiromi Shibuya; Hironori Matsumoto; Kiyotaka Nagahama; Junji Shibahara; Yoichi Kobayashi (Case Reports in Obstetrics and Gynecology)
In this case, a 66-year-old female patient presented with the chief complaint of abdominal distention. Computed tomography and magnetic resonance imaging revealed no enlarged ovaries or obvious primary lesions; however, massive ascites and peritoneal disseminated nodules were observed. Ascites cytology revealed adenocarcinoma and immunohistochemical findings suggested serous carcinoma. The patient then underwent tumor reduction surgery after preoperative chemotherapy for suspected Stage IIIC primary peritoneal carcinoma. Postoperative histopathology revealed carcinoma consisting mainly of high-grade serous carcinoma (HGSC) and sarcoma. In addition, serous intraepithelial carcinoma (STIC) of the fallopian tube was observed in the fimbriae of the left fallopian tube. Recently, it has been noted in the literature that most cases of peritoneal carcinoma are metastases or dissemination of carcinoma originating from the fimbriae of the fallopian tube. This is a rare case of peritoneal carcinosarcoma with STIC, and its report leads to a better understanding of the disease’s features and possible therapeutic approaches.